Understanding the Effect of Grown-in Defects in Silicon on Solar Cell Efficiency - Jinta Mathew; Bulent Arikan; Sercan Aslan; Ryan Bugeja; Davide La Fata; Jessica Magro; Vahdet Özyahni; Selin Seyrek; Nurhayat Yildirim; Daniele Zingariello; Marija Demicoli; Raşit Turan; et al. (SiliconPV Conference Proceedings)
Improving the efficiency of silicon-based solar cells is imperative to maximise harnessing of solar power. The current improvements in efficiency were attained by better manufacturing techniques and purer materials. There is however indirect evidence that the so-called agglomerated grown-in defects in silicon have a direct impact on cell efficiency and if this is the case, the efficiency could be improved by crystal engineering. This study focuses on understanding the defect generation and growth mechanisms in commercial silicon crystals and their impact on cell efficiency. Silicon wafers from different parts of the crystal having a range of oxygen and dopant concentrations and growth profiles, were investigated. These crystals were characterized using various tools and techniques such as Infrared Light Scattering Tomography (LST) to measure the defect density, and Fourier Transform Infrared Spectroscopy (FTIR) to measure the oxygen concentration. Solar cells were then fabricated out of these wafers to measure the performance of the devices. An understanding of why and how such defects impact the yield of different silicon wafers will lead to a thorough understanding of the relationship between the defect types, size and densities and cell efficiency. Moreover, this study will also shed light on the development of crystal recipes or after-crystal procedures to eliminate or minimize these effects on solar cell performance.